Proximal Point Algorithm Based on AP Iterative Technique for Nonexpansive Mappings in CAT(0) Spaces - Panwar, Anju; Jyoti; Mor, Prateek; Pinki (Communications in Mathematics and Applications, 2023)
In this paper, we introduce the modified proximal point algorithm for solving minimization problems in CAT(0) spaces. We then show that the sequence converges to a common fixed point of nonexpansive mapping and a minimizer of a convex function. Finally, we present a numerical illustration for supporting our main result. The findings in this paper are a generalization of certain corresponding results given by some authors.